2007
DOI: 10.2106/jbjs.e.01305
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Acetabular Periprosthetic Osteolytic Lesions Measured with Computed Tomography

Abstract: There is considerable variation in the rates of progression of the size of osteolytic lesions around stable acetabular components. Lesion size and the progression of lesion size are generally related to polyethylene wear rates, higher patient activity levels, and larger-diameter femoral heads. Osteolytic lesions measuring >10 cm(3) in volume are associated with a high rate of progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 25 publications
1
44
1
1
Order By: Relevance
“…The above findings are consistent with other investigators who have shown that the biological activity of particulate wear debris is strongly dependent on adherent endotoxin, 18 that ex vivo responses of human PBMCs to particulate stimuli can be affected by the presence of indwelling metallic prostheses, 19 and that polyethylene wear rate modulates both the risk of osteolysis, and the severity of osteolytic lesions. 6 For these reasons polyethylene wear rate and clinical titanium exposure were included as covariates in our multivariate analysis model. The observed differences pattern of gene expression between the subject groups remained significant for all cytokines studied after correction for the effects of these covariates.…”
Section: Immune Response In Osteolysis-susceptible Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above findings are consistent with other investigators who have shown that the biological activity of particulate wear debris is strongly dependent on adherent endotoxin, 18 that ex vivo responses of human PBMCs to particulate stimuli can be affected by the presence of indwelling metallic prostheses, 19 and that polyethylene wear rate modulates both the risk of osteolysis, and the severity of osteolytic lesions. 6 For these reasons polyethylene wear rate and clinical titanium exposure were included as covariates in our multivariate analysis model. The observed differences pattern of gene expression between the subject groups remained significant for all cytokines studied after correction for the effects of these covariates.…”
Section: Immune Response In Osteolysis-susceptible Patientsmentioning
confidence: 99%
“…5,6 Previous clinical studies have demonstrated elevated serum levels of proinflammatory cytokines in patients with active osteolysis after THA compared to healthy or osteoarthritis control subjects. 7,8 Peripheral blood mononuclear cells (PBMCs) taken from patients with active osteolysis show inducible cytokine responses in vitro that are greater than those from osteoarthritis subjects, 9 and the magnitude of these responses correlate with the severity of the associated clinical osteolytic lesion.…”
mentioning
confidence: 99%
“…For example, increased wear of the UHMWPE acetabular cups correlates with an increased rate of osteolysis [44,55,111]. However, those studies also showed that other factors modulate the biologic response to wear particles.…”
Section: Introductionmentioning
confidence: 99%
“…However, that study used plain radiographs to evaluate osteolysis and bone ingrowth. Multiple studies suggest radiographs underestimate the incidence and extent of osteolysis [10,14,19,27,28,34,38], and several authors state helical CT is the modality of choice to detect these lesions [19,26,32,34]. Thus, the true incidence of osteolysis with this implant is unclear.…”
Section: Introductionmentioning
confidence: 99%